Copy number-based quantification assay for non-invasive detection of PVT1-derived transcripts. - Gargi Pal; Olorunseun O Ogunwobi (PLoS ONE)
Background One of the most important susceptibility loci for cancer is the 8q24 human chromosomal region. The non-protein coding gene locus plasmacytoma variant translocation 1 (PVT1) is located at 8q24 and is dysregulated in prostate cancer. PVT1 gives rise to multiple transcripts which may have different functions. Here, we describe a real-time quantitative polymerase chain reaction (qPCR)-based assay for copy number-based quantitation of PVT1 exons 4A, 4B, and 9 to enable accurate, reproducible, and quantifiable detection. Methods PVT1 exons 4A, 4B, and 9 were cloned into a plasmid vector to create standards for subsequent creation of linear standard curves representing a broad range of concentrations. PCR was carried out using SYBR-Green signal detection to quantify PVT1 exons 4A, 4B, and 9. The efficacy of this assay was evaluated by using it to detect these transcripts in prostate epithelial and prostate cancer cell lines, normal and cancerous human prostate tissues, human serum, mouse plasma, and urine samples. Results The results indicate that the assay can be used to quantify both low and high copy numbers of PVT1-derived transcripts. This is the first report of a copy number-based quantification assay for non-invasive detection of PVT1 derived transcripts. Conclusions This novel assay holds promise for routine non-invasive testing in diseases where PVT1 is dysregulated.